PENGARUH PEMBERITAAN MEDIA MASA PADA KASUS DUGAAN KORUPSI DAN PARTISIPASI WARGA DALAM MENGGUNAKAN HAK PILIH DI PEMILUKADA SERENTAK DI INDONESIA - Gede Moenanto Soekowati (INJECT (Interdisciplinary Journal of Communication), 2018)
Democracy in Indonesia is steping forward and developing currently that could be seen through the general election from regional to national level. The development of democracy has been also influenced by media, in this context, media could mean the extension of people. Media include mass media, social media, and online media. The influence of media in society as a tool for participating for the general election and democracy could not be denied. The influence of media could be interfered by some parties such as politics, governments, and departments of law for justice. Those influence are not simply to demonstrate, but the implications are both explicitly and implicitly influence the communities in the way they participate in for using their right in the general election.